GM-CSF signalling blockade and chemotherapeutic agents act in concert to inhibit the function of myeloid-derived suppressor cells in vitro - Gargett, Tessa (Clin Transl Immunology, 2016)
Immune evasion is a recently defined hallmark of cancer, and immunotherapeutic approaches that stimulate an immune response to tumours are gaining recognition. However tumours may evade the immune response and resist immune-targeted treatment by promoting an immune-suppressive environment and stimulating the differentiation or recruitment of immunosuppressive cells. Myeloid-derived suppressor cells (MDSC) have been identified in a range of cancers and are often associated with tumour progression and poor patient outcomes. Pancreatic cancer in particular supports MDSC differentiation via the secretion of granulocyte-macrophage colony-stimulating factor (GM-CSF), and MDSC are believed to contribute to the profoundly immune-suppressive microenvironment present in pancreatic tumours. MDSC-targeted therapies that deplete or inhibit this cell population have been proposed as a way to shift the balance in favour of a tumour-clearing immune response. In this study, we have modelled MDSC differentiation and function in vitro and this has provided us with the opportunity to test a range of potential MDSC-targeted therapies to identify candidates for further investigation. Using in vitro modelling we show here that the combination of GM-CSF-signalling blockade and gemcitabine suppresses both the MDSC phenotype and the inhibition of T-cell function by MDSC.